Application Remote Sensing in Study Influence Of El Niño incident in 2015/2016 On the Amount of Rainfall in Sarawak - Kemarau, Ricky Anak; Valentine Eboy, Oliver (Journal of Techno-Social, 2021)
In 2015/2016 saw the country hit by El Niño which caused drought and drought all over the country. This El Nino incident caused a decrease in the amount of rainfall due to the movement of trade air currents. Many studies have been conducted on the effects of El Niño on temperature and rainfall. However, there is a discrepancy in the findings. The study area of ​​Sarawak experienced different natural disasters in February 2016, namely floods in South Sarawak and drought in North Sarawak. To understand this incident, researchers use rain data from remote sensing technology through Global precipitation Measurement (GPM) to provide rainfall distribution data during El Niño 2016 events. The first step to calculate the total of rainfall in a month from GPM data for gain the pattern amount rainfall during 2015/2016. The results of this study found that El Nino events caused a decrease of 20-30% during El Niño events even during the occurrence of the northeast monsoon. However, the effect of El Nino on the amount of rainwater distribution depends on the position of a district in Sarawak. The results of this study successfully show that the northern areas of Sarawak are much affected during El Nino which is important to those responsible in providing infrastructure to reduce the impact of El Niño, especially to the agricultural sector.